congenital hypothyroidism - Samingan, Nurshadia; Zaini, Azriyanti Anuar; Annie, Leong (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Childhood obesity is a rising health concern across the globe, with the risk of persisting in adulthood. Lifestyle modification remains the cornerstone of first-line management; however, achieving favourable weight or BMI outcomes remains challenging. The use of liraglutide, a glucagon-like-peptide 1 receptor agonist, has been shown to be safe and effective in children. This study describes the use of liraglutide in six paediatric patients with obesity, examining its effects on weight, BMI, and associated side effects. METHODOLOGY Data of six patients who were started on liraglutide in 2024 in the Paediatric Obesity Clinic were obtained through the hospital electronic medical records. Clinical and anthropometry details at the start of liraglutide and at the last clinic visit were recorded. Associated side effects of the medication were asked post-initiation of liraglutide. RESULT All six patients were males and extremely obese (BMI above 120% of 95th percentile). Patients were between 12.5 to 17.8 years old (median 15.5 years). Weight ranged from 75.8 kg to 115.2 kg (z-score 1.99 to 2.95) with median 101.9 kg. BMI ranged from 29.98 kg/m² to 40 kg/m² (z-score 2.14 to 2.67) with a median 35.8 kg/m². Patients were followed up for a minimum of 2 months and a maximum of 9 months (median 5 months). The median and percentage for weight and BMI reduction were –3.7 kg (4%) and –2.36 kg/m² (7%), respectively. Half of the patients were on a full dose of liraglutide (3 mg). No weight gain was observed, although 2 patients’ weight did not differ remarkably at the last visit. Highest weight and BMI reduction were –9.3 kg and –3.48 kg/m² respectively, seen in 2-months period in a 15.5-year-old male on 1.8 mg daily dose of liraglutide. Half of the patients experienced nausea, abdominal cramps and bloating. CONCLUSION The use of liraglutide in this small cohort showed some positive evidence to treat paediatric patients with extreme obesity. However, the long-term sustenance of maintaining favourable weight and BMI needs to be examined in the future.